PELAKSANAAN MUATAN KECAKAPAN ABAD 21 DALAM PEMBELAJARAN PADA MAHASISWA PROGRAM STUDI PENDIDIKAN LUAR SEKOLAH FKIP UNIVERSITAS RIAU - Yulia, Rara; ayub, Daeng; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is how high the 21st century skill load has been carried out on students from the School of Education Outside the FKIP University of Riau and how much is the contribution of 21st century skill content to students from outside the school education program FKIP Riau University. The benefit of this research is to find out the level of 21st century skill load on students of the outside education school program at the University of Riau FKIP has been carried out, determine the contribution of 21st century skills content to students from outside the school education program FKIP Riau University. This research is a descriptive study with a quantitative approach. The population in this study was the population in this study were the 2016 class which amounted to (64) people and the 2017 class which amounted to (57) people in the School of Education Study Program FKIP Riau University which amounted to 121 respondents. The sampling technique in this study is the Proportinate Stratified Random Sampling technique used when the population has members or elements that are not homogeneous and have proportional strata. The instrument in this study is a questionnaire or questionnaire containing statements about the implementation of 21st century skills content for students from outside the FKIP Riau University education program with indicators 1) Creativity, 2) Innovation, 3) Critical Thinking, 4) Problem Solving, ) Communicate, 6) Collaborate. The mean collaborates with the mean 4.38 and SD 0.42, then communicates with the mean 4.36 and SD 0.41, then innovates with the mean 4.29 and SD 0.37, then creativity with the mean 4.27 and SD 0, 31, then problem solving with mean 4.26 and SD 0.42, then think critically with mean 4.12 and SD 0.39. The meaning is to think critically low on 21st century skills in out-of-school education, but collaborate very high on the implementation of 21st century skills in out-of-school education.Key Words: Implementation, Content, 21st Century Skills